Genius Loci European Area of Old City of Surabaya: Challenges and Opportunities for Development (Literature Study) - Afini Nur Fajriyah; Suzanna Ratih Sari (Eduvest - Journal of Universal Studies, 2026)
The Old City of Surabaya is one of the historical areas established during the Dutch colonial period. Old Town Surabaya, with its unique architecture, spatial planning, and atmosphere, exudes a distinctive genius loci. The purpose of this paper is to provide analytical results related to the challenges and opportunities for development associated with the genius loci of the European area of Old Town Surabaya. This study adopts a qualitative research approach. The findings indicate that the Old Town Surabaya area features various forms of Dutch colonial architecture that embody rich historical and cultural values. Challenges in preserving the genius loci include development pressure and changes in function, degradation of authentic buildings, and minimal community participation. Meanwhile, opportunities for developing the area based on the genius loci include sustainable heritage tourism, adaptive reuse while maintaining character, a bottom-up approach to conservation, and multistakeholder collaboration.